2013
DOI: 10.1109/tsm.2013.2258411
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Materials Optimization for a TFET Device With Central Nothing Region on Insulator

Abstract: This paper presents the work regimes of an atypical SOI device. The proposed device belongs to the Tunneling FET class, but the main body is a vacuum cavity. Each layer has a maximum of 10 nm. Firstly, the paper studies the static characteristics of the proposed device by simulations for different semiconductor materials: Si, SiC and Ge, with different doping concentrations, in different bias conditions. Secondly, some key parameters are defined in order to establish the boundary of the different work regimes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Tunnel-FETs with horizontal p-i-n islands offer swing less than 60 mV/decade, surpassing the MOSFET limit [4], and vacuum microdevices still get minimum noise [5]. Recently, an alternative nanostructure composed by semiconductor-vacuum-semiconductor on insulator, also known as nothing on insulator (NOI) device, was proposed [6]- [8]. Due to the tunneling conduction through a vacuum cavity, besides to a configuration on insulator, the NOI device makes the link among vacuum, Silicon On Insulator (SOI), and tunnel devices.…”
Section: Introductionmentioning
confidence: 99%
“…Tunnel-FETs with horizontal p-i-n islands offer swing less than 60 mV/decade, surpassing the MOSFET limit [4], and vacuum microdevices still get minimum noise [5]. Recently, an alternative nanostructure composed by semiconductor-vacuum-semiconductor on insulator, also known as nothing on insulator (NOI) device, was proposed [6]- [8]. Due to the tunneling conduction through a vacuum cavity, besides to a configuration on insulator, the NOI device makes the link among vacuum, Silicon On Insulator (SOI), and tunnel devices.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the back and front gates from SOI architecture [12] are re-named here as bottom and top gates, accordingly to the TFT terminology, [6,7].…”
Section: The Organic-tft Conceptmentioning
confidence: 99%
“…Quantum-well MOSFETs [8] 81 InGaZnO-Based Thin-Film Transistor [9] 85 Al 0.83 In 0.17 N/AlN/GaN MOS-HEMT on SiC Substrate [10] 40 The nothing-on-insulator (NOI) transistor [11,12] 50 Metal-Ferroelectric-Insulator [13] 150 Double-Gate Strained-Ge Heterostructure Tunneling FET [14] 52 Fe-FET with P(VDF-TrFE)/SiO2 Gate Stack [13] 13 Metal-Ferroelectric-Metal-Oxide-Semiconductor FET [15] 46-58 Vertical Si-Nanowire n-Type Tunneling FETs [16] 30 would bring transformative change in the performance and energy efficiency of both ultra-low-power and high performance micro-/nano-electronic applications. We formally named this new device Silicon-on-Ferroelectric Insulator Field Effect (SOFFET) [20,21].…”
Section: Structurementioning
confidence: 99%
“…Using the structure of Fig. 2 we can derive a first order approximation of V TH as illustrated in (8)- (11). From the derived model (11), it is observed that the threshold voltage of the proposed PD-SOFFET depends on the thickness of the ferroelectric material.…”
Section: Threshold Voltage Of the Proposed Pd-soffetmentioning
confidence: 99%
See 1 more Smart Citation